Moulin mechanism design for freight consolidation. (October 2018) - Zhang, Wentao; Uhan, Nelson A.; Dessouky, Maged; Toriello, Alejandro
Highlights: A Moulin mechanism is proposed to solve a cost allocation problem in freight consolidation service. The mechanism determines the set of suppliers to be served as well as their cost shares. The truthfulness and approximate budget-balance of the mechanism are proved and discussed. The economic efficiency of the mechanism is studied using the social cost as the means of comparison. A both truthful and budget-balanced Moulin mechanism is proposed for the single truck scenario – the total demand of all suppliers fits into one truckload. Abstract: In freight consolidation, a "fair" cost allocation scheme is critical for forming and sustaining horizontal cooperation that leads to reduced transportation cost. We study a cost-sharing problem in a freight consolidation system with one consolidation center and a common destination. In particular, we design a mechanism that collects bids from a set of suppliers, and then decides whose demand to ship via the consolidation center and the corresponding cost shares. We use the Moulin mechanism framework to design a truthful mechanism for the cost-sharing problem, and study the mechanism's budget-balance guarantee and economic efficiency. We find that it is generally not possible to obtain a simultaneously truthful and budget-balanced Moulin mechanism under the transportation cost structure we study. For our proposed mechanism, there exists a trade-off between the budget-balance guarantee and the level of incentives that can be given to large suppliers. Additionally, the mechanism has better economic efficiency when there are more bidding suppliers or the destination is farther away. In our setting, either the consolidation center or the suppliers need to be subsidized. The parameters that determine the trade-off between the consolidation center's benefit and suppliers' cost savings should be set based on the specific goals of the consolidation center. Encouraging more suppliers to bid helps to increase the overall social welfare.